1994
DOI: 10.1159/000139234
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal Variation in the Acute Effects of Estradiol and Progesterone on Beta-Endorphin and Met-Enkephalin Levels in Specific Brain Regions of Ovariectomized Rats

Abstract: The present investigation was conducted to evaluate the effects of estradiol and progesterone on β-endorphin and Met-enkephalin levels in specific brain regions of ovariectomized rats. Female Sprague-Dawley rats (100-120 g) adapted to a 12-hour light, 12-hour dark illumination cycle were used in these studies. Animals were ovariectomized under pentobarbital anesthesia. After a recovery period of 10-14 days, estradiol (50 µg/kg in 0.2 ml olive oil) was administered subcutaneously to rats at either 8.00, 14.00 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1996
1996
2025
2025

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…Hence, just as opioid peptides modulate activity of the sex hormones, ste roid hormones can affect endogenous opioid function in the brain. In fact, findings from our laboratory indicate that estrogen and pro gesterone affect P-EN as well as ME levels in specific brain regions of ovariectomized rats and that these effects are diurnally controlled [18]. These findings are in agreement with previous findings which found that hypotha lamic P-EN contents fluctuate with a diurnal rhythm and that estradiol treatment alters the circadian changes in hypothalamic p-EN con tents in ovariectomized rats [19].…”
Section: Introductionsupporting
confidence: 92%
“…Hence, just as opioid peptides modulate activity of the sex hormones, ste roid hormones can affect endogenous opioid function in the brain. In fact, findings from our laboratory indicate that estrogen and pro gesterone affect P-EN as well as ME levels in specific brain regions of ovariectomized rats and that these effects are diurnally controlled [18]. These findings are in agreement with previous findings which found that hypotha lamic P-EN contents fluctuate with a diurnal rhythm and that estradiol treatment alters the circadian changes in hypothalamic p-EN con tents in ovariectomized rats [19].…”
Section: Introductionsupporting
confidence: 92%
“…Gonadectomy was performed in 45-day-old rats, as previously described (Fischer et al, 2008; Gordon & Soliman, 1994) under anesthesia induced by an intramuscular injection of a mixture of ketamine (55 mg/kg) and xylazine (5.5 mg/kg). A subcutaneous injection of ketoprofen (5 mg/kg) was used for postoperative analgesia (Roughan & Flecknell, 2000).…”
Section: Methodsmentioning
confidence: 99%
“…Hormone administration was performed by daily subcutaneous injection of 17 β-estradiol (50 μg/kg; Gordon & Soliman, 1994) or progesterone (8 mg/kg; He, Evans, Hoffman, Oyesiku, & Stein, 2004) in females and of testosterone propionate (1 mg; Campos, Morais Pde & Pupo, 2003) in males, during 7 days, as previously described (Fischer et al, 2008; Gordon & Soliman, 1994). At the seventh day, hormone injection was performed 1 hr prior to the TMJ injection of formalin (Fischer et al, 2008; Gordon & Soliman, 1994). Hormones were purchased from Sigma Chemical (St. Louis, MO) and dissolved in propylene glycol.…”
Section: Methodsmentioning
confidence: 99%
“…The procedure was performed in 45-day-old male rats through a single scrotal incision, as previously described (Fischer et al, 2008;Gordon & Soliman, 1994). The testicular bundles were ligated and removed and the skin was sutured.…”
Section: Gonadectomymentioning
confidence: 99%